The Reluctant Urbanist: Pierre Trudeau and the Creation of the Ministry of State for Urban Affairs - Spicer, Zachary (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d’études canadiennes, 2011)
In 1971 the Ministry of State for Urban Affairs began operations in Canada. The creation of the ministry was unprecedented and resulted in invaluable assistance to Canada’s municipalities. One of the major obstacles to the ministry’s creation, however, was Prime Minister Pierre Trudeau’s resistance to the idea of formal engagement with Canada’s cities. Trudeau would eventually relent and create the ministry, abandoning both his resistance to federal–urban engagement and his traditional conceptualization of federalism. This paper tracks the influences on Trudeau’s decision-making process, attempting to explain this policy reversal, while also detailing the change of attitude of Pierre Trudeau towards federalism in Canada.